VERIFIKASI LINIERITAS KURVA BAKU TESTOSTERON MENGGUNAKAN METODE ELISA (ENZYME-LINKED IMMUNOSORBENT ASSAY) - Fernanda, MA Hanny Ferry; Sa'adi, Ashon; Sudjarwo, Sudjarwo (Journal of Research and Technology, 2019)
ELISA (Enzyme-Linked Linked Immunosorbent Assay) is one of the quantitative analysis methods that is often used to determine the levels of active compounds in biological samples. In this study, we will verify the method of determining testosterone active compounds in blood and urine samples of female patients who have PCOS (Polycystic Ovary Syndrome) using the Human Testosterone ELISA Kit. Before conducting testosterone levels using ELISA, it is necessary to verify the linearity of the standard curve first to determine the effect of testosterone standard levels on the analyte response in the form of optical density. The linearity verification of the standard testosterone curve is calculated using linear regression calculations with the results of the coefficient of determination which is 0.978 with a value of α = 0.05. While for testing with the calculation of 4 parameter logistic (4PL), the results of the coefficient of determination are 0.999. Based on these results it can be concluded that the testosterone standard level has a significant influence on the response of optical density analytes.